Enhancing teacher competence in identifying student needs through NIMID at inclusive schools - Dudi Gunawan; Yoga Budhi Santoso; Prinanda Gustarina Ridwan; Hendriano Meggy; Juhanaini Juhanaini; Nandi Warnandi; Nazwa Laila Putri; Wanda Dwi Rahayu; Elvina Sabriyati (Inovasi Kurikulum, 2024)
Inclusive education prepares students to become global citizens who understand cultural, linguistic, and perspective diversity. This is in line with the principle of human rights, which affirms every individual's right to receive a decent education without discrimination. Inclusive education ensures that no student is neglected in the learning process. Competent teachers can create a compelling and quality learning environment. Need Identification Method Inclusive Design (NIMID) training is one way to improve understanding of inclusive education and teacher skills in designing inclusive learning programs. This study aims to measure the effectiveness of Needs Identification Method Inclusion Design (NIMID) training in improving teacher understanding. The experimental design method with a one-group pretest-posttest design was chosen to measure teacher understanding and skills. Non-parametric statistical tests with the Wilcoxon Signed-Rank Test were conducted to analyze the pretest-posttest results. The results showed that NIMID training improved teacher skills in the concept of inclusive education, identification, and assessment, and it was able to develop learning programs tailored to student's needs so that learning was optimal.    Abstrak Pendidikan inklusif mempersiapkan peserta didik menjadi warga dunia yang memahami keberagaman budaya, bahasa, dan perspektif. Hal ini sejalan dengan prinsip hak asasi manusia yang menegaskan hak setiap individu untuk mendapatkan pendidikan yang layak tanpa diskriminasi. Pendidikan inklusif memastikan tidak ada siswa yang diabaikan dalam proses pembelajaran. Guru yang kompeten mampu menciptakan lingkungan belajar efektif dan berkualitas. Pelatihan Need Identification Methode Inclusive Design (NIMID) salah satu cara untuk meningkatkan pemahaman pendidikan inklusif dan keterampilan guru dalam mendesain program pembelajaran inklusif. Penelitian ini bertujuan untuk mengukur tingkat keefektifan pelatihan Needs Identification Method Inclusion Design (NIMID) untuk meningkatkan pemahaman guru. Metode desain eksperimen dengan desain one-group pretest-posttest dipilih untuk mengukur pemahaman dan keterampilan guru. Uji non-parametric statistical dengan Wilcoxon Signed-Rank Test dilakukan untuk menganalisis hasil pretest-posttest. Hasil penelitian menunjukkan bahwa pelatihan NIMID berdampak pada peningkatan kemampuan guru dalam konsep pendidikan inklusif, identifikasi dan asesmen, serta mampu menyusun program pembelajaran yang disesuaikan dengan kebutuhan peserta didik sehingga pembelajaran menjadi optimal. Kata Kunci: kompetensi guru; kebutuhan belajar peserta didik; pelatihan Need Identification Methode Inclusive Design (NIMID)